MOTIVATING POTENTIAL OF GROUPING LEARNERS (A2 LEVEL) - G. Yersultanova; М. Jandildinov; Zh. Zhyltyrova; M. Aimagambetova; A. Baktiyar (Scientific Journal of Pedagogy and Economics, 2023)
The purpose of the study was to investigate the possibility of collaborative learning in English language classrooms to develop students’ grammar and reading skills and motivations. A pre — experimental-post-test group design was used to differentiate the effect of the cooperative learning approach on reading and grammar skills with standard full-class teaching and two components of learning motivation: intrinsic and instrumental. Before and after the end of the experiment, the findings of this study were collected at different points in order to determine the effect of collaborative learning on grammar and reading skills and motivations. Reading and grammar abilities were checked first using an English diagnostic test before and after certain collective learning activities, in realistic terms. The sociometric questionnaire was then conducted to the study to identify the interactions between the learners and the use of collaborative learning in English lessons. Another survey also was conducted to determine the type of motivation (intrinsic) of the learners. The results were assessed by utilizing basic and inferential statistical methods including mean scores, standard deviations, independent sample t-tests and pairs. The findings showed impressive improvements in grammar and reading skills after the implementation of collaborative learning methods. Given the findings, the researchers propose that teachers may gain from applying collaborative learning in English classes, which in turn may increase students’ grammar and reading skills and motivation.